Holocene Temperature Variations in Semi-Arid Central Mongolia—A Chronological and Sedimentological Perspective From a 7400-year Lake Sediment Record From the Khangai Mountains - Bliedtner, Marcel; Strobel, Paul; Struck, Julian; Salazar, Gary; Szidat, Sönke; Nowaczyk, Norbert; Bazarradnaa, Enkhtuya; Lloren, Ronald; Dubois, Nathalie; Haberzettl, Torsten; Zech, Roland (Frontiers in Earth Science, 2022)
Semi-arid Mongolia is a highly sensitive region to climate changes, but the region’s Holocene paleoclimatic evolution and its underlying forcing mechanisms have been the subject of much recent debate. Here we present a continuous 7.4 ka sediment record from the high-altitude Shireet Naiman Nuur (Nuur = lake) in the central Mongolian Khangai Mountains. We extensively dated the sediments and analyzed elemental composition and bulk isotopes for lake sediment characterization. Our results show that 14C-dating of bulk organic carbon and terrestrial macrofossils provide a robust and precise chronology for the past 7.4 ± 0.3 cal. ka BP at Shireet Naiman Nuur and 14C-ages are mostly in stratigraphic order. The 14C-based chronology is confirmed by paleomagnetic secular variations, which resemble the predictions of spherical harmonic geomagnetic field models. The very good chronological control makes paleomagnetic secular variation stratigraphy a powerful tool for evaluating and refining regional 14C chronologies when compared to the record presented here. The lake sediment proxies TOC, N, log (Ca/Ti) and log (Si/Ti) reveal increased lake primary productivity and high growing season temperatures from 7.4 ± 0.3 to 4.3 ± 0.2 cal. ka BP, which is likely the result of stronger summer insolation and pronounced warming. Reduced summer insolation thereafter results in decreased productivity and low growing season temperatures at Shireet Naiman Nuur from 4.3 ± 0.3 cal. ka BP until present day. The globally acknowledged 4.2 ka event also appears as a pronounced cooling event at Shireet Naiman Nuur, and additional abrupt cooling events occurred during minima in total solar irradiance at ~3.4, 2.8 and 2.4 ka BP. Low lake primary productivity and growing season temperatures are likely the result of longer ice cover periods at the high-altitude (2429 m a.s.l.) Shireet Naiman Nuur. This leads to shorter mixing periods of the lake water which is supported by more positive δ13CTOC because of increased incorporation of dissolved HCO3- by aquatic producers during periods of longer ice cover.